Medical sociology topics on the pages of the Sociološki pregled/ Sociological review - Šuvaković, Uroš V. (Sociološki pregled, 2018)
The paper presents research results about the representation of medical sociology topics in the journal Sociološki pregled/Sociological Review from 1938 to 2017. It offers a classifcation of the thematic felds of published papers. Starting from the hypothesis that the situation in periodicals reﬂects the development level of an academic discipline and in view of the duration of the period considered here, the paper concludes that medical sociology remains an inadequately developed branch of sociology in Serbia, unlike one of its subdisciplines - sociology of mental health, which is the result of traditional academic reasons and the difference in their representation at institutions of higher education in Serbia.